1992
DOI: 10.1128/jb.174.7.2111-2120.1992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a fixLJ-regulated Bradyrhizobium japonicum gene sharing similarity with the Escherichia coli fnr and Rhizobium meliloti fixK genes

Abstract: We describe the cloning, sequencing, regulation, and mutational analysis of a Bradyrhizobium japonicum fixK-like gene whose product belongs to the family of Fnr-Crp-related regulatory proteins. The predicted 237-amino-acid FixK protein was found to share between 28 and 38% sequence identity with the Escherichia coli Fnr protein, other bacterial Fnr-like proteins (FnrN, Anr, and HlyX), and two rhizobial FixK proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 58 publications
1
67
1
Order By: Relevance
“…Furthermore, three genes encoding small, homologous Hsps have recently been described (hspA, hspB, and hspC ; Narberhaus et al, 1996). Other genes are duplicated, as was reported for nodD (Gö ttfert et al, 1992), fixK (Anthamatten et al, 1992;Fischer, 1994), and for another sigma factor, namely 54 (Kullik et al, 1991 (Landick et al, 1984); Citrobacter freundii, Serratia marcescens, Agrobacterium tumefaciens, and Zymomonas mobilis (Nakahigashi et al, 1995); Haemophilus influenzae (Fleischmann et al, 1995); Vibrio cholerae (J. Das, unpublished; Accession No. U44432); Pseudomonas aeruginosa (Benvenisti et al, 1995;Naczynski et al, 1995); Caulobacter crescentus (Reisenauer et al, 1996;Wu and Newton, 1996); Myxococcus xanthus RpoC (Apelian and Inouye, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, three genes encoding small, homologous Hsps have recently been described (hspA, hspB, and hspC ; Narberhaus et al, 1996). Other genes are duplicated, as was reported for nodD (Gö ttfert et al, 1992), fixK (Anthamatten et al, 1992;Fischer, 1994), and for another sigma factor, namely 54 (Kullik et al, 1991 (Landick et al, 1984); Citrobacter freundii, Serratia marcescens, Agrobacterium tumefaciens, and Zymomonas mobilis (Nakahigashi et al, 1995); Haemophilus influenzae (Fleischmann et al, 1995); Vibrio cholerae (J. Das, unpublished; Accession No. U44432); Pseudomonas aeruginosa (Benvenisti et al, 1995;Naczynski et al, 1995); Caulobacter crescentus (Reisenauer et al, 1996;Wu and Newton, 1996); Myxococcus xanthus RpoC (Apelian and Inouye, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being homologous to nitrogen fixation regulatory proteins in other bacteria, strains with mutations in this gene are still Nif ϩ (1). Nevertheless, Anthamatten et al (1) have suggested that this protein is involved in the regulation of other oxygen-responsive systems, such as hydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…The cultures were incubated, with the flasks shaken and the test tubes on a rotary wheel. Similar protocols have been used to study oxygen effects on expression of other B. japonicum genes (3,31). For the time course experiment whose results are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In nodules, this oxygen control is likely to occur via the same two-step regulatory cascade already shown to control nif and fix genes in various rhizobial species. These oxygen-regulated genes are activated via the FixLJ two-component regulatory system (1,3,10,25). FixL (17,34), the sensor, is a hemoprotein that under low-oxygen conditions transmits a signal via phosphorylation to the response regulator, FixJ (20,41), which in turn activates specific nif and fix genes (30,45,59,60).…”
mentioning
confidence: 99%
See 1 more Smart Citation